The (in) feasibility of Intermunicipal Public Consortia for Solid Waste Management in Amazonas, Brazil (Research, Society and Development, 2020)
The present study aimed to strategically analyze the implementation of an intermunicipal public consortium for the integrated management of solid waste (CPIGRS) between two municipalities in Amazonas State, considering the technical, economic, environmental, social and political dimensions. The research is descriptive in terms of objectives, bibliographic, documentary and field regarding procedures and a qualitative and quantitative approach. The data were obtained through the application of online questionnaires, forms, in semi-structured interviews and preparation of technical maps. Indicators were defined for the evaluation of the implementation of CPIGRS, with the adoption of the Delphi Method, and at the end of the consultations, 30 indicators were defined. Subsequently, the areas for the possible construction of landfills were delimited and the costs that each municipality would have had to be raised if an embankment were constructed in an isolated and intercropped manner. After analyzing the dimensions related to CPIGRS and classifying them in the defined indicators, the municipalities showed a viability of 94.4%. The study revealed that there are benefits in the five dimensions if CPIGRS is implemented. However, it is emphasized that the economic and political dimensions may be responsible for the failure to implement consortia in the State, mainly for maintaining a high value for the construction of a landfill as well as for the lack of priority for municipal managers to equalize the problems of waste in their respective municipalities.